Effects Of Yogic Interventions On Cardiopulmonary And Endothelial Health At High Altitude: A Prospective Longitudinal Interventional Study (Applied Biological Research, 2023)
High-altitude sojourn may lead to risk factors for high-altitude disorders and  subsequent altitude sickness. This study was aimed to analyse the effects of sea level yoga practices on individuals when they ascend to high altitudes (HAs).  Healthy male subjects were randomly divided into two groups i) yoga group (n  = 43) and ii) control group (n = 44). One month of yoga training was given to the  yoga group for 30 min daily. The control group was provided daily routine for  one month. Blood samples were collected when subjects were in fasting condition  at sea level and at high altitude. Thepulmonary function, blood pressure,  cardiovascular and resting metabolic parameters and estimated markers of  endothelial homeostasis were monitored at sea level and then at high altitude.  The study revealed that yoga group had enhanced pulmonary functions (p
Keywords: Altitude; blood pressure; cardiopulmonary health; hypoxia; yoga